Drying Parameters of Half-Cut and Ground Figs (Ficus carica L.) var. Mission and the Effect on Their Functional Properties - Juan José Martínez-García; José Alberto Gallegos-Infante; Nuria Elizabeth Rocha-Guzmán; Patricia Ramírez-Baca; María Guadalupe Candelas-Cadillo; Rubén Francisco González-Laredo (Journal of Engineering)
Drying of ground and half-cut figs (Ficus carica L., var. Mission) was investigated at three temperatures (45, 55, and 65°C). Their effective moisture diffusivity () was estimated by using the slope method. values for ground figs were 5.15 × 10−10, 9.96 × 10−10, 1.07 × 10−9 m2 s−1 and for half cut figs 5.88 × 10−10, 1.66 × 10−9, and 2.08 × 10−9 m2 s−1 at 45, 55, and 65°C, respectively. Dehydrating fig samples showed a similar behavior: higher values at higher temperatures and activation energy () values in the range of other foodstuffs. Half-cut figs needed about twice more energy and time than ground figs to carry out the dehydration; values were 56.86 and 28.21 kJ mol−1, respectively. The drying process increased the total phenolic content and degraded the anthocyanin content of figs; however, it enhanced the dried figs antioxidant activity. Dehydrating ground figs was faster and maintained its functional properties better than half-cut figs.